Development plans and participatory budgets: The precarious of a complex reform of the State - López Ricci, José (2004)
"A silent, and in my opinion revolutionary, reform of the budget, to truly become a management tool and an instrument for short-term economic and social programming." This is how the participatory budget was cataloged by a senior official from the Ministry of Economy and Finance. "They are a disaster, with this spending has been atomized... In addition, the MEF has acted against the law", affirms emphatically and harshly -and as a balance, a year later- the main person in charge of the National Decentralization Council (CND).